Dietary and lifestyle interventions in ADPKD – a review of current literature - Skweres, Martyna; Pucyło, Szymon (Quality in Sport, 2025)
Background and aim. Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary nephropathy. The only approved therapeutic option is tolvaptan, which has limited availability. Disease-modifying interventions are a topic of strong interest, and with growing understanding of metabolic pathways that are disrupted in ADPKD, new therapeutic possibilities are being explored. This review discusses the promising role of dietary and lifestyle interventions in management of ADPKD. Materials and methods. The paper analyzes studies in databases such as PubMed, Google Scholar, ResearchGate, and other scientific databases. Clinical trials, double-blind randomized controlled trials, meta-analyses, systematic reviews, and other review articles were included in the study. Conclusions. Among interventions that have established disease-modifying potential in pre-clinical studies are dietary interventions leading to induction of ketosis, which has been shown to slow cyst growth in pre-clinical studies. However, little is known about long term benefits and safety of such interventions. Increased water intake and low salt consumption also have the potential to slow cystogenesis, but current research remains inconclusive regarding their efficacy. Lifestyle interventions such as physical activity and cessation of smoking play an important role in management of common comorbidities and help improve quality of life. Further research is necessary in order to establish optimal dietary treatment that corresponds to ADPKD patients’ specific metabolic needs.